Gelfand-Shilov Smoothing Effect for the Radially Symmetric Spatially Homogeneous Landau Equation under the Hard Potential $γ=2$ (Journal of Partial Differential Equations, 2021)
Based on the spectral decomposition for the linear and nonlinear radiallysymmetric homogeneous non-cutoff Landau operators under the hard potential $γ=2$ in perturbation framework, we prove the existence and Gelfand-Shilov smoothing effect for solution to the Cauchy problem of the symmetric homogenous Landau equation with small initial datum.